Dixon Sustainability - Arco Montero, José María del (2025)
The sustainability of the planet depends on the conservation and expansion of forest stands. In the process of oak colonisation, some species of rodents collaborate by scattering and bury acorns. Our aim is to study these relationships for each pair of species. Therefore, we want to know if Algerian mouse (Mus spretus), wood mouse (Apodemus sylvaticus) and common vole (Microtus arvalis) participate in the dissemination of acorns of 5 oak species. Departamento de ciencias Agroforestales